RESPON PERTUMBUHAN BAMBU CINA (Bambusa multiplex) TERHADAP PEMBERIAN MEDIA PUPUK HAYATI ECOFERT - Saiful Rahmadani; Eny Dwi Pujawati; Adistina Fitriani (Jurnal Sylva Scienteae, 2022)
Chinese bamboo has advantages like other bamboos, it has many roots, produces dense clumps, is able to prevent soil erosion and is a source of oxygen. This bamboo plant can be used as handicrafts, one of which is as a sketch and accessories. The purpose of this study was to analyze the effect of giving the best Ecofert biofertilizer on the growth of Chinese bamboo with the parameters of survival percentage, shoot growth and shoot height increase. This research method was carried out using a completely randomized design (CRD) which consisted of 5 different treatments, namely 1) treatment A without the application of Ecofert biofertilizer; 2) treatment B application of 10 grams of Ecofert fertilizer; 3) treatment C with 20 grams of Ecofert fertilizer; 4) treatment D application of 30 grams of Ecofert fertilizer; 4) treatment E was the application of 40 grams of Ecofert fertilizer. From each treatment, the observation of the live percentage got a value ranging from 65% to 85%, the highest result at the end of the observation was the average increase in the number of shoots in treatment E (40 grams) with the results of getting 3.12 shoots and at the average increase in shoot height the results the highest treatment B (10 grams) with the result 159.92 cmBambu cina memiliki kelebihan seperti bambu lainnya memiliki perakaran yang banyak, menghasilkan rumpun yang rapat, mampu mencegah erosi tanah dan penghasil sumber oksigen. Tanaman bambu ini dapat dijadikan kerajinan tangan salah satunya sebagai sketsel dan aksesoris. Tujuan penelitian ini agar dapat menganalisis pengaruh pemberian pupuk hayati Ecofert terbaik terhadap pertumbuhan bambu cina dengan parameter persentase hidup, pertambahan tunas dan pertambahan tinggi tunas. Metode penelitian ini dilakukan dengan Rancangan Acak Lengkap (RAL) yang terdiri dari 5 perlakuan berbeda yaitu 1) perlakuan A tanpa pemberian pupuk hayati Ecofert; 2) perlakuan B pemberian pupuk Ecofert 10 gram; 3) perlakuan C pemberian pupuk Ecofert 20 gram; 4) perlakuan D pemberian pupuk Ecofert 30 gram; 4) perlakuan E pemberian pupuk Ecofert 40 gram. Dari setiap perlakuan pengamatan dari persentasi hidup mendapatkan nilai kisaran 65% sampai 85%, hasil tertinggi diakhir pengamatan dari rata-rata pertambahan jumlah tunas pada perlakuan E (40 gram) dengan hasil mendapatkan 3,12 tunas dan pada pertambahan rata-rata tinggi tunas hasil tertinggi perlakuan B (10 gram) dengan hasil 159,92 cm.